Can someone help me to break down exactly the order of execution for the following versions of flatten? I'm using Racket.
version 1, is from racket itself, while version two is a more common? implementation.
(define (flatten1 list)
(let loop ([l list] [acc null])
(printf "l = ~a acc = ~a
" l acc)
(cond [(null? l) acc]
[(pair? l) (loop (car l) (loop (cdr l) acc))]
[else (cons l acc)])))
(define (flatten2 l)
(printf "l = ~a
" l)
(cond [(null? l) null]
[(atom? l) (list l)]
[else (append (flatten2 (car l)) (flatten2 (cdr l)))]))
Now, running the first example with '(1 2 3) produces:
l = (1 2 3) acc = ()
l = (2 3) acc = ()
l = (3) acc = ()
l = () acc = ()
l = 3 acc = ()
l = 2 acc = (3)
l = 1 acc = (2 3)
'(1 2 3)
while the second produces:
l = (1 2 3)
l = 1
l = (2 3)
l = 2
l = (3)
l = 3
l = ()
'(1 2 3)
The order of execution seems different. In the first example, it looks like the second loop (loop (cdr l) acc)
is firing before the first loop since '(2 3) is printing right away. Whereas in the second example, 1 prints before the '(2 3), which seems like the first call to flatten inside of append is evaluated first.
I'm going through the Little Schemer but these are more difficult examples that I could really use some help on.
Thanks a lot.
See Question&Answers more detail:
os 与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…